KEPRIBADIAN TOKOH ADARA DALAM NOVEL ARIAL DAN ADARA KARYA HELOBAGAS: ANALISIS PSIKOLOGI SASTRA - Najiah Khairun Nurhaliza; Dicky Rachmat Pauji; Kurnia Rachmawati (Jurnal Edukasi Khatulistiwa: Pembelajaran Bahasa dan Sastra Indonesia)
This study aims to describe the psychological character of Adara in the novel Arial and Adara by HeloBagas through the Id, Ego, Superego aspects approach, as described in Sigmund Freud's thought. By using descriptive qualitative method with data collection techniques of reading and note-taking, it can produce psychological aspects that appear in internal and external problems, moral decisions, and social considerations of Adara's character. This study can also answer if the novelist consciously and unconsciously incorporates elements of Sigmund Freud's thoughts into the narrative of the story in this novel. The results of this study are expected to contribute and further understanding of the influence of literary psychology theory.